Analisis Faktor-Faktor yang Mempengaruhi Praktik Income Smoothing - Giovanni Regina Gondokusumo; Merry Susanti (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This research aims to explain the effect of board independence, profitability, leverage, firm size and managerial ownership on income smoothing of manufacturing companies listed in Indonesia Stock Exchange over the period of 2017-2020. This research used 42 companies as its samples that were selected by purposive sampling techniques with 168 data in total for four years and were analyzed using logistic regression through EViews 10 as the medium for the data processing. The data which were used in this research are secondary data obtained from the financial statements. Sample companies in this research were classified using Eckel Index into smoothed companies and non-smoothed companies. The results conclude that profitability and managerial ownership have negative impacts on the practice of income smoothing. On the other hand, board independence, leverage and firm size have no impacts on the practice of income smoothing.